Pendampingan Proses Pembelajaran Siswa MI Ma’rifatul Ulum Secara Blended Learning serta Pemanfaatan Powerpoint sebagai Alternatif Bahan Ajar Guru - Anita Anita; Canti Tresnaratih; Dwi Indri Nurfadhila; Salsa Dilla Ardhana (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
Student mentoring when studying is something that is needed, it becomes an effort so that students can achieve their goals in learning. In assisting students, it is also carried out in order to foster self-confidence, have a sense of comfort when learning, grow attitudes and behaviors that are creative, innovative and desire to move forward. Because in an effort to achieve learning goals it is not easy so that learning intentions are needed that grow in the child himself, so that children can think well. The age of students, especially at the elementary school level, is where children need concrete objects in every delivery of material delivered by the teacher. The concrete forms given by the teacher will make it easier for students to reason or imagine something, it can also be something interesting and fun. Through this Thematic Real Work Lecture (KKN-T), I assisted students which was carried out at Mi Ma'rifatul Ulum, Kec. Kaliwedi, Kab. Cirebon. This is an effort to achieve goals in learning and make power point media as an alternative for teachers in delivering a material, aiming for the concept of the material being taught to be responded well by students